2020
DOI: 10.1371/journal.pone.0229757
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of HIV related opportunistic infections after initiation of highly active antiretroviral therapy at Ayder Referral Hospital, Mekelle, Ethiopia: A retrospective single centered cohort study

Abstract: Introduction Even though use of antiretroviral therapy (HAART) decreases the incidence of opportunistic infections (OIs) they are continuing to be a major cause of morbidity and mortality. Studies concerning this problem are scarce in Eastern Africa. The aim of this study was to determine the incidence and predictors of OIs after initiation of HAART in Ethiopia. Methods A health facility based single centered cohort study using structured data extraction sheet was conducted. The study population was all HIV po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
26
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 17 publications
3
26
1
1
Order By: Relevance
“…This result is in line with a study conducted in Mekelle Ayder referral hospital, which reported tuberculosis (32.3%) as the highest proportion among the other OIs. 13 The reason for higher number of tuberculosis in our study could be due to only 45.8% of PLWHIV took IPT. Lower IPT intake is associated with increased incidence of tuberculosis.…”
Section: Discussionmentioning
confidence: 63%
See 3 more Smart Citations
“…This result is in line with a study conducted in Mekelle Ayder referral hospital, which reported tuberculosis (32.3%) as the highest proportion among the other OIs. 13 The reason for higher number of tuberculosis in our study could be due to only 45.8% of PLWHIV took IPT. Lower IPT intake is associated with increased incidence of tuberculosis.…”
Section: Discussionmentioning
confidence: 63%
“…This finding is higher than the previous Ethiopian study conducted in Ayder Referral Hospital (7.5 cases/100 person-years). 13 This higher figure might be attributed to significant number of patients followed in this study had poor ART drug adherence and were at advanced stages of HIV/AIDS which could probably elevate the incidence. In addition, sample size variations between the two studies could contribute for this difference.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…Opportunistic infections (OIs) associated with HIV remain the single main cause of ill-health and death among HIV/AIDS patients in resource poor settings , therefore HIV positive patients in resource poor settings continue to suffer from (8). Evidence of studies conducted in different parts of Ethiopia had documented that, the incidence of OIs after HAART was increased in especially among hospitalized HIVpatients (9,10) and, reported the prevalence of OIs among HIV infected patients in the range of 33.3% in Addisa Abeba to 88% in Dawro Zone . Tuberculosis (TB), oral candidacies, Pneumocystis Carini Pneumonia (PCP), bacterial pneumonia, Herpes Zoster, Cryptococcus meningitides, Persistent diarrhea, kaposi´s sarcoma and lymphoma are the most reported common opportunistic infections in HIV patients in Ethiopia (15,17,18), but major differences in spectrum of OIs observed across the country.…”
Section: Introductionmentioning
confidence: 99%